A Case of Late Spontaneous Post–Radial Keratotomy Corneal Perforation Managed With Specialty Lenses. (September 2018) - Van den Heurck, Jonas; Boven, Kim; Anthonissen, Lieselotte; Van Hoey, Maarten; Koppen, Carina
Abstract : Purpose: To describe a case of spontaneous wound dehiscence 29 years after radial keratotomy (RK) and to illustrate how specialty contact lenses were used for tectonic support and optic correction. Setting: Tertiary referral center for corneal pathology. Design: Case report. Results: In November 2014, a 62-year-old woman presented to the emergency department with a spontaneous corneal perforation in her left eye. Her ocular history was significant only for uncomplicated RK surgery performed in 1985 to correct myopia (−5.50 D) in both eyes. At the slit-lamp pronounced, bullous edema was seen in the inferotemporal quadrant of the left cornea with internal opening of the 3.30- and 5-o'clock positions incisions and severe localized thinning and aqueous leakage at the 5-o'clock position incision. There was no history of trauma. A conservative approach was adopted: application of a standard bandage lens was effective in tamponading the leakage, allowing the anterior chamber to reform; a custom-made soft lens was worn for tectonic support over a period of 4 months. Finally, visual acuity was restored to 20/20—by fitting a scleral lens. Conclusion: Spontaneous corneal perforation is a rare but more dramatic long-term complication after RK. The pivotal role of appropriately fitted soft bandage lenses in the conservative management of this type of complex perforation is highlighted. For optical correction, a scleral lens was fitted with excellent visual result, illustrating the added value of specialty contact lenses as an alternative to surgery in the management of postrefractive corneas.